(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2020)
The settlements’ infrastructure development, aimed at satisfying, first of all, the needs of motorists, is accompanied by powerful negative changes in the conditions of human life. Now problems of providing conditions for moving by individual environmental vehicles, pedestrian traffic and, in particular, for the low-mobility groups of the population are becoming more relevant. In the article is analyzed and summarized the world experience of urban street-road network reconstruction in accordance with the change of priorities that has occurred in the theory of transport planning. It singled out 2 basic options for the redistribution of space between pedestrians, cyclists, public and private transport: 1) narrowing of lanes for private transport; 2) reducing the number of lanes for private transport